Effectivity of Rosella Flower Pressed Water (Hibiscus sabdariffa L.) as a Natural Coloring Agent for Examination of Feces Confirmed Helminthiasis - Sulistyo, Ayu Indah; Aisyah, Riandini; Nurhayani, N; Mahmudah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Soil Transmitted Helminths (STH) are prevalent in tropics. Eosin 2% dye is commonly used for helminth egg identification, but this dye is carcinogenic and damaging to the environment. Aim: This study evaluates the effectiveness of rosella pressed water (Hibiscus sabdariffa L.) as a natural dye for helminthiasis feces examination, examines its performance with added citric acid, and compares the staining results. Methodology: This experimental study used a post-test only control group design with 27 purposively selected samples of 10% formalin-fixed helminthiasis feces. Staining was performed using rosella pressed water at concentrations of 10%, 20%, 30%, and 40%, with and without 9% citric acid, alongside 2% eosin as a comparison. Observations were made under a 10x microscope, and staining effectiveness was evaluated using a Likert scale by a parasitologist. Results: The staining quality of rosella pressed water was consistent (median = 3) across all concentrations. Parasite visualization varied without citric acid, with reduced quality at 20% concentration (median = 2). Preparation quality remained stable (median = 3). Kruskal-Wallis analysis showed no significant differences (p > 0.05). Discussion: Rosella flowers (Hibiscus sabdariffa L.) contain anthocyanin pigments which are flavonoid compounds that provide red to purple color, so they can be used as a natural dye for STH eggs. Conclusion: This study showed that rosella flower pressed water was effective for STH egg staining, although 2% Eosin gave the best and most consistent results. There were no significant differences between treatments.